Perlakuan Akuntansi Merger Padapt Indosat Ooredoo Hutchison : (Studi Kasus Merger PT Indosat Ooredoo dan Hutchison 3 Indonesia Tahun 2022) - Inayah Atifah, Zahra; Angelina Lahura; Aurelia Viesna Bota Werang; Nur Anita Chandra Putry; Umi Wahidah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
The concept of corporate mergers in the telecommunications industry is an important strategy for dealing with fierce competition and the need for large network investments. In addition to navigating changes in operations and business, mergers also have a complex impact on accounting aspects, particularly in the recognition of assets, liabilities, and goodwill in accordance with PSAK 22 on Business Combinations. This study uses a qualitative-descriptive approach with a case study method on the merger between PT Indosat Ooredoo and Hutchison 3 Indonesia, which was successfully completed in 2022. The data used comes from financial reports, annual reports, and various official company publications before and after the merger. The results show that the merger had a positive impact on increasing revenue, EBITDA, and the number of customers, but also caused short-term profit fluctuations due to an increase in depreciation expenses and integration costs recognized in accordance with PSAK 22. The application of PSAK 22 plays an important role in improving the transparency and reliability of financial statements after the merger, although it also adds complexity in assessing the company’s financial performance.